How do you find the product #(6y-13)(6y+13)#?

2 Answers

Answer:

#(6y-13)(6y+13)=36y^2-13^2#

Explanation:

Given-

#(6y-13)(6y+13)#

It is like #(a-b)(a+b)#

#(a-b)(a+b)=a^2-b^2#
#(6y-13)(6y+13)=(6y)^2-13^2=36y^2-13^2#
#(6y-13)(6y+13)=36y^2-13^2#

May 29, 2017

Answer:

(#36##y^2#-#169#)

Explanation:

#All# of us #know# #the# formula

(#a^2##-##b^2#)#=#(#a##+##b#) (#a##-##b#)
#by# putting #a##=#(#6##y#) #&# #b##=#(#13#)

after the successful substitution we will bet that#:-#
(#36##y^2#-#169#)